Analysis of digital literacy skills of 2nd semester students at Citra Bangsa University in facing the challenges of the Society 5.0 era - Abani, Gilbert Michael; Beatrice Sogen, Maria Magdalena; Ibrahim, Muhammad Al-Gifari; Nule, Emanuel Natalino (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to evaluate the digital literacy skills of second-semester students at Universitas Citra Bangsa in addressing the challenges presented by the Society 5.0 era. In this era, individuals are expected not only to utilize technology effectively but also to think critically, act ethically, and adapt to the continuously evolving digital ecosystem.The research employed a descriptive quantitative method, focusing on five key areas of digital literacy: the use of information and communication technology (ICT), access to digital information, communication through digital media, critical thinking related to digital content, and ethical behavior in digital environments.The findings indicate that most students demonstrated moderate to high levels of digital literacy, particularly in ICT utilization and digital communication. However, weaknesses were identified in critical thinking and ethical application of technology.These results highlight an urgent need to improve the curriculum and implement more targeted digital literacy programs to equip students with more comprehensive digital competencies. Developing these skills is crucial to preparing students for a highly connected, technology-driven higher education environment in the Society 5.0 era.